Disseminating clinical study results to trial participants in Ethiopia: insights and lessons learned - Degaga, TS; Weston, S; Tego, TT; Abate, DT; Aseffa, A; Wayessa, A; Price, RN; Hailu, A; Thriemer, K (BioMed Central, 2020)
International regulatory authorities and funders require that research be disseminated promptly and appropriately to all involved stakeholders. However, following completion of clinical trials participants often either do not receive any feedback or materials provided are not appropriate for the context. The investigators of a multicentre anti-malarial clinical trial (the IMPROV study) conducted a dissemination meeting at one of the study sites in Ethiopia; trial participants and medical staff were provided feedback on the study results. This report summarizes the dissemination strategies adopted by the investigators, including a plain language visual aid and simple communication techniques. Lessons learned are reported with a discussion on the operational challenges to dissemination of clinical trials in resource limited settings.